Upbeat nystagmus: a clinical and pathophysiological review - Marcelli, Vincenzo; Giannoni, Beatrice; Volpe, Giampiero; Faralli, Mario; Marcelli, Edoardo; Cavaliere, Michele; Fetoni, Anna Rita; Pettorossi, Vito Enrico (Frontiers in Neurology, 2025)
Finding a vertical nystagmus, especially when looking straight ahead, should alert the neurologist/neuro-otologist for other signs of cerebellar or brainstem dysfunction. Upbeat nystagmus (UBN) is a relatively uncommon neuro-otological finding that clinicians may encounter in patients presenting with vertigo. This phenomenon is closely linked to central vestibular dysfunction, making it essential for healthcare providers to recognize and interpret it promptly. Accurate identification of UBN can significantly aid in directing patients toward the appropriate diagnostic and therapeutic pathways. As our understanding of UBN’s pathophysiology has advanced, the clinical significance of this sign has become increasingly evident. It is now recognized that UBN can occur as an isolated finding or more frequently as part of a broader spectrum within defined clinical syndromes. This expanded knowledge has also opened the door to various therapeutic approaches tailored to the underlying cause. In our study, we want to provide as accurate a picture as possible about the origins and clinical presentations of UBN.